Upaya Meningkatan Motivasi Belajar Matematika dengan Memberikan Layanan Bimbingan Kelompok bagi Siswa Kelas IX.1 SMPN 9 Kota Tangerang Selatan - Watiah (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Motivation is a person’s encouragement consciously or unconsciously to do an activity to achieve its goals. Motivation can also come from within and from other people, be it teachers, family and friends. Various efforts can be made to motivate students in mathematics, including optimizing counseling and guidance services, especially group guidance services. It is intended that through group guidance, students will feel themselves part of the group so that cooperation is needed in getting things done. This study aims to determine the increase in student motivation through group guidance services. This research method uses the Class Action Research (CAR) method with 2 cycles. Collecting data in the form of observations (observations) by filling out the student motivation observation sheet. With a sample of students who get less math scores totaling 10 students. Based on the results of the research that has been done, it shows that the student’s motivation before the cycle has an average student interest of 39.69% in the very low category. the average student interest in the first cycle the average level of student interest is 51.41% in the medium category, the second cycle is 73.44% with high criteria. Based on the results of the implementation of the Classroom Action Research (CAR) method in cycle 1 and cycle 2, students’ motivation to take part in group guidance services has increased. Thus, from the implementation of classroom action research carried out in 2 cycles, it was concluded that there was an increase in student motivation to follow group guidance services at SMP Negeri 9 Tangerang Selatan City in learning activities.